Posttraumatic symptomatology in children exposed to war - Vizek-Vidović, Vlasta; Kuterovac-Jagodić, Gordana; Arambašić, Lidija (2000)
The study examines affective and behavioral symptomatology of two groups of school-age children being to a different degree traumatized during the war against Croatia (N=1034). Six self-reported questionnaires were used to assess number and type of survived war experiences, PTSD symptoms, anxiety, depression, psychosomatic symptoms and psychosocial adaptation. Canonical discriminant analysis yielded significant discriminant function that indicates moderate differentiation between the two groups of children according to the assessed symptoms. Results of the 2 x 2x 2 ANOVAs (gender x age x level of traumatization) indicate that childrens reactions to war traumata vary in respect to all those factors, and their interaction. Results indicate that gender differences are more prominent in older children. Older girls report more posttraumatic stress reactions, anxiety and depression, but also it seems that they are better adapted than boys. Younger children, particularly those who survived more war events, report more PTSD symptoms than older children.
Projekt MZOS
ENG